KAJIAN INFRASTRUKTUR SEBAGAI DASAR PENGEMBANGAN KAWASAN MINAPOLITAN DI KABUPATEN INDRAMAYU - Rohjan, Jajan; Ummah, Tri Mar’atul; Syarifudin, Deden; Tou, Harne Julianti (Universitas Galuh, 2023)
The minapolitan area comprises one or several centers of rural production activities such as fishery production systems and management of specific natural resources and agribusiness. Regional functional connectivity and hierarchy in spatial units are the most important in maintaining administrative, institutional, and business systems. In the Decree of the Minister of Number KEP.32/MEN/2010 and the Decree of the Regent of Indramayu Number 523/Kep. 24-Diskanla/2011, Indramayu Regency was designated as the location for constructing the Minapolis area. Indramayu Regency is an area that has excellent potential for fisheries and marine production, with a production yield of over 150,000 tons per year. However, this situation is not matched by the availability of adequate infrastructure with a lack of supporting infrastructure in the Minapolitan area, where downstream production is growing. The purpose of this study is to assess the infrastructure of the Minapolitan area as a basis for developing the infrastructure of the Minapolitan area in the form of development directions. The method used is mixed, where the analysis is based on quantitative aspects while strengthening the justification is carried out qualitatively. The results obtained from this study show that the development of regional productivity development needs to be integrated with an adequate infrastructure development plan. Infrastructure development is based on the partial needs of fishermen groups and sector authorities that handle them. The grand design of the Minapolitan area is not carried out by the local government either with a cooperation scheme or a vertical assistance scheme. Infrastructure development is carried out with the capacity of the district government itself. Therefore, priority infrastructure deficiencies include fish seed centers, hatcheries, springs, cold storage, fish auctions, and accessibility between regions.